Radio-frequency transistors from millimeter-scale graphene domains - 魏子钧 傅云义 刘竞博 王紫东 贾越辉 郭剑 任黎明 陈远富 张酣 黄如 张兴 (Chinese physics B, 2014)
Graphene is a new promising candidate for application in radio-frequency （RF） electronics due to its excellent elec- tronic properties such as ultrahigh carrier mobility, large threshold current density, and high saturation velocity. Recently, much progress has been made in the graphene-based RF field-effect transistors （RF-FETs）. Here we present for the first time the high-performance top-gated RF transistors using millimeter-scale single graphene domain on a SiO2/Si substrate through a conventional microfabrication process. A maximum cut-off frequency of 178 GHz and a peak maximum os- cillation frequency of 35 GHz are achieved in the graphene-domain-based FET with a gate length of 50 nm and 150 nm, respectively. This work shows that the millimeter-scale single graphene domain has great potential applications in RF devices and circuits.